Model Kontingensi Keefektifan Kepemimpinan: Kontroversi dan Relevansi - Lina Anatan (Jurnal Manajemen Maranatha, 2011)
Contingency Model of Leadership Effectiveness introduced by Fried E. Fiedler arose in response to limitations in the two major questions focused on in leadership study at that time; what the personality factors are which make someone a leader; and what the personality traits are which make them effective. It shows the relationship between the leader's orientation or style and group performance under different situational conditions. The leadership style variable is measured using an instrument called least preferred coworker (LPC). The model is based on determining the orientation of the leader (relationship or task), the elements of the situation (leader-member relations, task structure, and leader position power), and the leader orientation that was found to be most effective as the situation changed from low to moderate to high control. Acccording to Fiedler's Model, task oriented leaders is more effective in low and moderate control situations, while relationship oriented leaders were more effective in moderate control situations. The model and its supporting researches were evaluated from empirical, methodological, and theoretical perspectives and indicated that the hypothesis of the model was not conclusively supported, numerous methodological shortcomings were pointed out, and when the theoretical scheme underlying the model was analyzed, and a new scheme was proposed. This article is a literature reviews on contingency model of leadership effectiveness's critics and it's relevance in todays research's issue on leadership effectiveness.Keywords: contingency model, task oriented, relationship oriented, situational conditions, least preferred coworker